A cross-sectional study on neonatal morbidities and birth defects in diabetic pregnancies in Malaysia : a single hospital study - Ramdzan, Muhammad Yusoff Mohd (2018)
Background: National data regarding the neonatal outcome of infants of diabetic mothers is lacking despite Malaysia having one of the highest incidences of diabetic pregnancies in the region. This study aimed to describe the various neonatal morbidities and birth defects in infants of diabetic mothers and analyse their risk factors. Methods: In this cross-sectional, descriptive study spanning four months, antenatal history, neonatal morbidities and birth defects were assessed in the neonates of 292 diabetic mothers. Independent t-test and binary logistic regression were performed to determine the association of various risk factors with neonatal morbidities and with birth defects. Results: 94 (32%) infants had neonatal morbidities. 26 (9%) of them had severe morbidities. Mean third trimester HbA1c was 5.9%. Infants with neonatal morbidity had statistically higher mean third trimester HbA1c level (6.45 ± 1.36%) compared to infants without neonatal morbidity (5.53 ± 0.97%), p = 0.003. Every 1% increase in HbA1c increases the odds of having neonatal morbidity by 2.2 times (p <0.001). Third trimester HbA1c <6.5% will not affect the odds of having neonatal morbidities. 10 (3%) infants had major birth defects (including neural tube defects, congenital heart disease, various syndromes, perineal malformation). 27 (9%) had minor birth defects. There was no significance between pregestational HbA1c and birth defects. Conclusions: Despite good antenatal glycaemic control, current antenatal practices for GDM is suboptimal as evidenced by the high incidence of neonatal morbidity. Universal screening, emphasis on maternal education, accessible assessment tools and stricter glycaemic control (HbA1c <6.3) will lead to a better pregnancy outcome. Further studies documenting similar neonatal outcomes will make a stronger case for a review of the national guidelines.